Faktor-Faktor yang Mempengaruhi Kemampuan Auditor dalam Mendeteksi Kemampuan Auditor Mendeteksi Kecurangan (Literatur Review) - Hadija, Sitti; Kuntadi, Cris (Jurnal Ekonomi Manajemen Sistem Informasi, 2023)
This article reviews the factors that influence the auditor's ability to detect fraud, the variables studied are: competence, audit experience and professional skepticism, a study of audit literature. The purpose of writing this literature review article is to build a hypothesis on the influence between variables for use in further research. The method of writing this article is descriptive qualitative and literature review. The results of this literature review article are: 1) Competence has a significant effect on the Auditor's Ability to Detect Fraud; 2) Audit Experience has a significant effect on the Auditor's Ability to Detect Fraud; and 3) Professional skepticism has a significant effect on the auditor's ability to detect fraud.